Living Semantic and Pragmatic Aspects: A Reading in Shakespeare's ROMEO AND JULIET - Ali Hamada Mgallad (PROSPECTIVE RESEARCHES, 2023)
Parallel to his outstanding literary career, Shakespeare is incomparable in terms of language and linguistics. The unique structures, coinages, and other innovations that he presented in the line of his writings clearly show his authority over English which he masters unrivaled. This research is an attempt to show how Shakespeare tackled some major linguistic aspects, and to try to assess his approach to them. Semantics and pragmatics are applied there in his work and they are closely connected to the characterization. It is to follow an intriguing experiment, analyze its components and see how it works. Basically, it is intended to highlight a strategy that Shakespeare made use of by embodying a linguistic aspect in a character letting the character to stand for it. Human representations of linguistic aspects are set masterly in ROMEO AND JULIET in a way that allows us to get sufficient information about the extent to which linguistic characterization is essential for Shakespeare. For him, language and communication are bound to characterization which creates harmony and compatibility and gives more credibility to the characters.